2020
DOI: 10.1515/jpm-2020-0539
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with adverse fetal outcomes in pregnancies affected by Coronavirus disease 2019 (COVID-19): a secondary analysis of the WAPM study on COVID-19

Abstract: Objectives: To evaluate the strength of association between maternal and pregnancy characteristics and the risk of adverse perinatal outcomes in pregnancies with laboratory confirmed COVID-19. Methods: Secondary analysis of a multinational, cohort study on all consecutive pregnant women with laboratoryconfirmed COVID-19 from February 1, 2020 to April 30, 2020 from 73 centers from 22 different countries. A confirmed case of COVID-19 was defined as a positive result on real-time reverse-transcriptase-polymerasec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
48
0
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 7 publications
2
48
0
7
Order By: Relevance
“…They included 41 patients with SARS‐CoV‐2 infections, reporting that, among these, there was a 41.1% prevalence of preterm delivery < 37 weeks, 14.6% had pre‐eclampsia, 18.8% had preterm prelabor rupture of the membranes and in 7% there was perinatal death. A different report from the same authors 48 , analyzing 266 pregnant women who were positive for SARS‐CoV‐2, from 73 different centers and 22 countries, showed a prevalence of 26.3% ( n = 70) for preterm delivery, 2.3% ( n = 6) for stillbirth, 4.1% ( n = 11) for perinatal death and 3.8% ( n = 10) for fetal growth restriction. They explained that the increased rate of perinatal mortality was most probably related to prematurity.…”
Section: Discussionmentioning
confidence: 95%
“…They included 41 patients with SARS‐CoV‐2 infections, reporting that, among these, there was a 41.1% prevalence of preterm delivery < 37 weeks, 14.6% had pre‐eclampsia, 18.8% had preterm prelabor rupture of the membranes and in 7% there was perinatal death. A different report from the same authors 48 , analyzing 266 pregnant women who were positive for SARS‐CoV‐2, from 73 different centers and 22 countries, showed a prevalence of 26.3% ( n = 70) for preterm delivery, 2.3% ( n = 6) for stillbirth, 4.1% ( n = 11) for perinatal death and 3.8% ( n = 10) for fetal growth restriction. They explained that the increased rate of perinatal mortality was most probably related to prematurity.…”
Section: Discussionmentioning
confidence: 95%
“…The peculiar changes occurring in the cardiorespiratory system during pregnancy may be partially responsible of the increased burden of maternal morbidities observed in these women when compared to the non-pregnant general population. 2 , 3 , 4 , 5 Currently, although vaccinal programs are opened to pregnant women, there are still reports of a poor acceptance rate in this category of patients. 6 , 7 …”
Section: Introductionmentioning
confidence: 99%
“…Since the beginning of the pandemic, pregnancy has been claimed to represent an independent risk factor for severe disease. Several systematic reviews and large observational cohorts have reported a higher risk of severe respiratory symptoms, need for mechanical ventilation, and admission to intensive care units in pregnant women with SARS‐CoV‐2 infection compared with non‐pregnant women 6‐8 …”
Section: Introductionmentioning
confidence: 99%